Factores de riesgo que influyen en el desarrollo de enfermedades neurológicas en adultos mayores atendidos en el Centro de Salud Barreiro, periodo noviembre 2023-abril2024. - Rivera Zapata, Jamiles Estefanía (2024)
The present curricular integration work placed special emphasis on the risk factors that influence the development of neurological diseases in older adults, because it is a high-impact problem today. The objective was to determine the risk factors that influence the development of neurological diseases in older adults treated at the Barreiro health center, period November 2023- April 2024. This research was carried out with a qualitative approach, exploratory and inductive method. Data collection was carried out through the implementation of observation sheets to a population of 25 older adults and a questionnaire to 5 health professionals; intended to obtain relevant information on the subject of research. It is recommended to foster interdisciplinary collaboration between health professionals, social services, and the community to improve the quality of care and promote the comprehensive well-being of this population. It was concluded that the research carried out at the Barreiro Health Center has allowed to identify and analyze the risk factors that influence the development of neurological diseases in older adults, highlighting the complexity and interrelationship of biological, psychosocial and environmental aspects in the neurological health of this vulnerable population.